REFLEXÕES SOBRE A CONSTRUÇÃO SOCIAL DO BELO - Noberto Ramalho, Cristiano Wellington; Patrícia dos Santos, Andreia (Prometheus - Journal of Philosophy., 2020)
Based on the notion of aesthetics expressed in the testimonies of artisanal fishermen and on-site observations made about this group, the present text aims to reflect on the social construction of the beautiful, focusing on the theoretical production on the theme. The idea is also to postulate a theoretical way to account for a typical aesthetic of the artisanal fishing world.